(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
ZigBee has a wider range of applications. Three frequency bands of operation that ZigBee operates at are the 868-MHz, 915-MHz, and industrial unlicensed 2.4-GHz, scientific, and medical (ISM) bands. Out of three, this 2.4GHz band is an unlicensed band hence its very attractive and is commonly available throughout the world. The typical low data rate applications include those for home automation and industrial, commercial uses, consumer electronics, personal health care appliances peripherals and as well as for toys and games which are able to run for five months to two years on just batteries. Hence these areas of applications motivated to design A CMOSPA operating at 2.4GHz.In this work a single ended multistage cascode feedback linear power amplifier used and implemented it in .18um technology. Also, an efficient matching network is designed in order to get maximum efficiency, multistage for higher gain and feedback is designed to get linear output power and reliability is also more. The power amplifier operates at 2.4 GHz frequency meeting with the desired specifications.